Human Resource Training in Artificial Intelligence: A Necessity for Capacity Building in Nigerian University - Ofor-Douglas, Stella (Kashere Journal of Education, 2025)
This paper examines human resource training in Artificial Intelligence: A necessity for capacity building in Nigerian University. Artificial intelligence (AI) has been known to transform industries globally and its impact in education is very profound. Nigerian universities, which are vital vessels to national progress must harness AI to elevate and standardise its research and teaching. Artificial intelligence is gradually being integrated in human resource management and is vital in transforming the way Nigerian universities operate on a day to day basis. In order to remain competitive and bring value on the global stage, human resource professionals in universities must develop the necessary skills to harness Artificial Intelligence potential. This paper stands to highlighted the necessity for capacity building in Nigerian universities, focusing on AI training for human resource professionals. Several problems serve as a barrier for which AI can be integrated for human resource training in universities. The problems such as infrastructure deficits, policy gaps, low technical capacity and adapting to the evolving AI landscape. It is worthy to note that unless these problems are addressed there is no way forward for human resource training. The government, industry and the university itself all have their roles to play in solving these problems and ensuring capacity building in the university.